Healthy Tooth Generation: Interactive Oral Health Education Using Digital Media for Students of SMA Bina Jaya Kertapati Palembang - Mellani Cindera Negara; Sulistiawati Sulistiawati; Trisnawaty K; Danica Anastasia (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Oral health problems remain a major public health issue in Indonesia, particularly among adolescents, who often have limited knowledge and inappropriate toothbrushing practices. SMA Bina Jaya Kertapati Palembang is a senior high school located in a densely populated urban area, with most students coming from lower-middle socioeconomic backgrounds and having limited access to oral health education and services. This community service program aimed to improve students’ literacy and preventive behavior related to dental and oral health through interactive health education. The team developed a digital educational video titled “Generasi Sehat Gigi” (Healthy Tooth Generation), which delivered basic concepts of oral health, correct toothbrushing techniques, recommended brushing times, and the negative impacts of poor oral hygiene. The program was implemented through classroom-based sessions combining video screening, explanation, live toothbrushing demonstrations, and interactive discussions. The activity involved 31 second-grade students and was conducted on 4 November 2025 at SMA Bina Jaya Kertapati Palembang. High levels of enthusiasm and active participation, reflected in students’ relevant questions and engagement during practice, indicated an increase in awareness and motivation to maintain oral health. This program demonstrates that school-based, interactive, media-supported education can serve as an effective strategy to strengthen oral health literacy and foster healthy habits among adolescents.